European Company Survey, 2013 - European Foundation for the Improvement of Living and Working Conditions (2015)
Abstract copyright UK Data Service and data collection copyright owner.The European Company Surveys (ECS) are conducted by the European Foundation for the Improvement of Living and Working Conditions (Eurofound), an autonomous agency of the European Union, funded from the general budget of the European Commission. The aims of the ECS are to map, assess and quantify information on workplace policies and practices across Europe in a harmonised way and – to a lesser extent – to monitor developments over time. The ECS has been carried out every four years since 2004. It is a questionnaire-based representative sample survey carried out by telephone in the language(s) of the country. Interviews take place with the manager responsible for human resources in the establishment and when possible with an employee representative. The first ECS (known as the Establishment Survey on Working Time and Work-Life Balance, 2004-2005, held under SN 5655) covered workplace practices with regard to working time arrangements and work-life balance. The second ECS, carried out in 2009 (SN 6568), looked at different forms of flexibility as well as accompanying human resource management practices and the nature and quality of workplace social dialogue. The third ECS (SN 7735), carried out in spring 2013, looked at practices with regard to work organisation, human resources management, employee participation and social dialogue in European workplaces. Further information about the ECS can be found on the Eurofound European Company Surveys webpages. The third ECS: The main focus of the third ECS was on work organisation, Human Resources (HR) practices, employee participation and social dialogue. The survey, carried out in the spring of 2013 across 32 countries (27 EU Member States and Croatia, Former Yugoslav Republic of Macedonia, Iceland, Montenegro and Turkey), mapped a number of practices used in European workplaces, as well as how they are discussed and negotiated at workplace level as well as some of their outcomes. Main Topics: The ...